Uterine artery embolization following venous arterial malformation after abortion; A case report - Zahra Barati; Azim Moatamedfar (Mashhad University of Medical Sciences, 2021)
Introduction: Uterine artery malformation is a rarely condition in late bleeding after a cesarean delivery or curettage in women at reproductive age. The patient may face severe and repeated vaginal bleeding that threatens her life. This report introduces a case of uterine artery embolization caused by an arteriovenous malformation (AVM) in a woman, eight weeks after spontaneous abortion. Case presentation: The patient was a 35-year-old woman G1P1 referred to one of the hospitals of Ahvaz claiming severe vaginal bleeding. The patient had 8 weeks spontaneous abortion 40 days ago. AVM was diagnosed by Doppler ultrasonography. The patient underwent uterine artery embolization due to repeated bleeding and failure to control it, and also low parity. Conclusion: It is crucial to diagnose vascular malformations at the initial stages in patients with abnormal uterine bleeding. Embolization is the first and best choice for women who wish to preserve their fertility.